RELATIONSHIP BETWEEN THE BABY'S BIRTH WEIGHT AND THE INCIDENCE OF PERINEAL TEARING - Leni Suhartini; Hesti Kusumaningrum; Ni Nyoman Sulasmi; Tiara Resty (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2022)
Childbirth is a physiological process and an important event in life that is often remembered by a woman throughout her life, where birth trauma most often occurs is the perineum. A perineal tear is a perineal laceration that occurs when the baby is born either naturally or through an episiotomy. This study aims to determine the relationship between the baby's birth weight and the level of perineal tear in mothers with normal delivery. The research method is quantitative with a cross-sectional analytical research design. The sample is 298 people. Data were collected by looking at the maternity room register book from January-December 2021. Data were analyzed with the help of Software Statistics Product and Service Solutions (SPSS) Version 25. Research Results: from 298 deliveries there were 256 respondents who experienced perineal tears. 97 respondents to a grade 1 tear (32.6%), 156 respondents to a grade 2 tear (52.3%) and 3 respondents to a grade 3 tear (1%). Of the 298 mothers who gave birth, there were 256 deliveries with perineal tears with 206 (85.5%) baby weight <3365gr and 50 (87.7%) baby weight >3366 grams. Meanwhile, for mothers who experienced an intact perineum, there were 42 respondents where the baby's weight < 3365 g was found as many as 35 respondents (14.5%) and the baby's weight > 3366 there were 7 respondents (12.3%). The results of the chi-square test at = 0.05 obtained p = 0.821 (P> 0.05) this means that there is no relationship between the baby's birth weight and the incidence of perineal tears. Conclusion: there is no relationship between baby's birth weight and the incidence of perineal tears.